2018
DOI: 10.1093/mnras/stx3070
|View full text |Cite
|
Sign up to set email alerts
|

Massive outflows driven by magnetic effects – II. Comparison with observations

Abstract: The driving mechanism of massive outflows observed in high-mass star-forming regions is investigated using three-dimensional magnetohydrodynamics (MHD) and protostellar evolution calculations. In our previous paper, we showed that the mass outflow rate depends strongly on the mass accretion rate onto the circumstellar disk around a highmass protostar, and massive outflows may be driven by the magnetic effect in highmass star-forming cores. In the present study, in order to verify that the MHD disk wind is the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 76 publications
2
21
0
Order By: Relevance
“…Magnetohydrodynamical (MHD) simulations show that jets and molecular outflows are common in massive YSOs and that they have an important role in the formation process (e.g., Tan et al 2014;Matsushita et al 2018). For instance, Banerjee & Pudritz (2007) showed that early outflows can reduce the radiation pressure allowing the further growth of the protostar.…”
Section: 2015;mentioning
confidence: 99%
“…Magnetohydrodynamical (MHD) simulations show that jets and molecular outflows are common in massive YSOs and that they have an important role in the formation process (e.g., Tan et al 2014;Matsushita et al 2018). For instance, Banerjee & Pudritz (2007) showed that early outflows can reduce the radiation pressure allowing the further growth of the protostar.…”
Section: 2015;mentioning
confidence: 99%
“…XXXV 2016;Planck Collaboration Int. XXXIII 2016;Matsushita et al 2018;Beuther et al 2018). Large-scale observations (∼1 pc) of the magnetic field revealed a well-ordered structure in the lowdensity envelopes of molecular clouds, suggesting that parsecscale envelopes are magnetically supported against gravitational collapse (e.g., Franco et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We employ the same numerical code as in Machida & Hosokawa (2013), assuming spherical accretion onto the protostar (Hosokawa & Omukai 2009). While we use a different stellar evolution code in Matsushita et al (2018) and Machida & Hosokawa (2020), an advantage of the current method is that the evolution of the stellar radius only depends on the accretion history, not on other control parameters (see Section 3 in Matsushita et al 2018). The details in modeling the protostellar evolution do not affect our conclusions anyway (e.g.…”
Section: Stellar Evolution and Termination Condition Of Simulationmentioning
confidence: 99%